2020
DOI: 10.37358/rc.20.5.8150
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Antimalarial Test of Artocarpin and in vitro Antimalarial Test of Artonin M Isolated from Artocarpus

Abstract: The derivative of flavonoid compounds, artocarpin (1) and artonin M (2), were isolated from the root wood of Artocarpus altilis and from the root bark of A. kemando, respectively. Both plants originated from Lampung, Indonesia. The structure of the two compounds has been carefully determined by physical method and spectroscopy techniques of UV, IR, and NMR. The in vivo antimalarial test of artocarpin showed very good Plasmodium activity in female mice, with ED50 value of 34.88 mg/kg body weight (kgBW), whereas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…The results of fractionation with the VLC process showed that a separation was present between semi-polar components and non-polar components, resulting in seven combined fractions, namely E21 (fr.1-10; 23 mg), E22 (fr.11; 439.5 mg), E23 (fr.12; 1,336 mg), E24 (fr.13), E25 (fr.14-15), E26 (fr. [16][17][18][19], E27 (fr.20-23; 1,675 mg). All these fractions were screened for antibacterial activity using the agar diffusion method, and the results obtained were tabulated in Table 3.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of fractionation with the VLC process showed that a separation was present between semi-polar components and non-polar components, resulting in seven combined fractions, namely E21 (fr.1-10; 23 mg), E22 (fr.11; 439.5 mg), E23 (fr.12; 1,336 mg), E24 (fr.13), E25 (fr.14-15), E26 (fr. [16][17][18][19], E27 (fr.20-23; 1,675 mg). All these fractions were screened for antibacterial activity using the agar diffusion method, and the results obtained were tabulated in Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…According to their chemicals profile analyzed by TLC and their proton NMR spectrum, these fractions were grouped and combined into seven primary fractions, E21 (fr.1-10), E22 (fr.11), E23 (fr.12), E24 (fr.13), E25 (fr.14-15), E26 (fr. [16][17][18][19], E27 (fr.20-23) (Figure 2). All fractions E21-E27 were tested for their antibacterial property separately using disc diffusion and microdilution methods.…”
Section: Bioassay-guided Separation Of Ethyl Acetate Extractmentioning
confidence: 99%
See 1 more Smart Citation
“…antibacterial [12], antiplatelet [13], antifungal [14], antimalarial [15], anti-aging [16], and cytotoxic [17].…”
Section: Introductionmentioning
confidence: 99%
“…The therapeutic effect is associated with the abundance of phenolics, such as flavonoids, stilbenoids, dihydrochalcones, dihydrobenzoxanthones and prenylated flavonoids [12]. Single metabolites reported in vivo antimalarial [13], inhibition of LPS-induced inflammation [14], α-glucosidase inhibitory [15], TRAILresistance overcoming with antiviral [16], and anticancer [17] activities. Alkylated flavonoid Artonin E from A. elasticus also revealed considerable cytotoxic effect in MCF-7 human breast cancer cells by ROS mediated mitochondrial pathway [18,19].…”
Section: Introductionmentioning
confidence: 99%